2022
DOI: 10.1111/ffe.13698
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for fatigue damage detection in adhesive joints modified with nanoparticles under different temperatures

Abstract: Scarf adhesive joints (SAJs) in carbon fiber composites were fabricated with 5° taper angle and bondline thickness of 0.17 mm. The joints are modified with SiC‐nanoparticles and characterized through tensile and fatigue loading at room temperature (RT) and 50°C. The analysis of the hysteresis loop in terms of loss and storage moduli, potential and dissipated energies, and damping factor is a quite new topic and one of the important goals of this study. At RT, the fatigue limit of the SAJs was improved by 55% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Hence, the phase shift angle (δ) is computed by subtracting the "h" values of the strain and the stress equations. Khashaba et al 16,52 found good agreement between the predicted phase shift angle (δ) using equation (25) and that calculated using equation ( 6) via the developed Excel codes.…”
Section: Tensile Propertiesmentioning
confidence: 83%
See 3 more Smart Citations
“…Hence, the phase shift angle (δ) is computed by subtracting the "h" values of the strain and the stress equations. Khashaba et al 16,52 found good agreement between the predicted phase shift angle (δ) using equation (25) and that calculated using equation ( 6) via the developed Excel codes.…”
Section: Tensile Propertiesmentioning
confidence: 83%
“…The current study built on the insights of Khashaba et al 16,52 who have validated the estimated damping factors from the developed Excel codes by fitting the measured sinusoidal stress and strain data to the following sine functionwhere k, a, and b are coefficients and θ is the cycle angle (0 to 2 π ), and h is the horizontal shift angle. When h is added to θ, the maximum stress (or strain) occurs at π / 2 , 3 π / 2 and the minimum at 0, π , 2 π .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, nanostructures find application in composite materials, where one or more phases, having a nanometer scale, are embedded in a matrix. In terms of their matrix, nanocomposites are generally classified as [3]: ceramic-matrix [4][5][6][7][8][9][10][11][12], metalmatrix [13][14][15][16][17][18][19][20][21] and polymer-matrix nanocomposites [22][23][24][25][26][27][28]. More recently, research on cement-based materials (including concrete, mortar and cement paste) [29][30][31][32][33][34][35] has been trying to exploit the synergies that nanostructures can provide in terms of both improvement of their performance and acquisition of "smart" functions, making cement-based products become electric/thermal sensors or crack repairing materials [36].…”
Section: Introductionmentioning
confidence: 99%